The effect of tofu liquid waste on mortality and histopathology of goldfish (Cyprinus carpio) kidney as a biology alternative material concept for senior high school X grade - Ria Mayasari (University of Muhammadiyah Malang, 2017)
Liquid waste of tofu is a liquid-byproduct of tofu production proces which is known as